BENCHMARK FOR DETERMINATION OF FORCED MONEY IN EXECUTION OF STATE ADMINISTRATIVE COURT JUDGMENT - Muhammad Ali; Ardilafiza Ardilafiza; Jonny Simamora (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
The purpose of this research is to study about Benchmark Determination of the Administrative Court Decision Execution Forced In. Research methods used in this thesis is a research type normative and descriptive analytical research specifications, and approaches used, namely, the approach Law and approach cases. From the research we concluded that since when the claimant may apply for money of enforced at the time of the initial filing a lawsuit to the Administrative Court, for their money forced / Dwangsom in a decision of the State Administrative Court, it is motivated by a petition of Plaintiff in the lawsuit to beg loading money forced / Dwangsom Defendant if lost and wayward implement administrative court ruling, benchmark application is the amount of money forced the ruling stating Plaintiff granted, judgment and decision condemnatoir who has obtained permanent legal force. Because implementing administrative court ruling is always Agency / Administrative Officers are still active, more effective and efficient if the imposition of forced currency / dwangsom taken / deducted from salaries / allowances officials concerned each month. So it is not charged to the State finances forced money order imposing sanctions / dwangsom and administratively feasible, must be followed by concrete implementing regulations relating to money forced / dwangsom to sync with the Administrative Court Act and the Law on Government Administration.